THE POLITICS OF SOCIAL POLICY OF DIRECT CASH ASSISTANCE OF VILLAGE FUNDS (BLT DD) AS POVERTY REDUCTION EFFORT IN PANDEMIC PERIODS IN INDONESIA - Nafirotul Karima; Laila Kholid Alfirdaus; Teguh Yuwono (Institut Pendidikan Tapanuli Selatan, 2023)
This research tried to explore the social policy of the Direct Cash Assistance of Village Fund. As the COVID-19 or SARS-CoV-2 was first detected and began to develop at the end of 2019 in Wuhan, China, it did not stop spreading to almost all countries in the world throughout 2020. The diseases that attack the respiratory organs have made more than 590 million people worldwide infected with this virus. In Indonesia, the pandemic caused several major impacts in all sectors, such as the health sector, the economic sector, the education sector, the religious sector, and others. In fact, the implementation of PSBB and PPKM policies can reduce the economic growth and cause many people losing their jobs, thereby it potentially increasing the number of poor people. In the context of handling and anticipating the impact of the COVID-19 pandemic, the Government has launched several social safety net programs, one of which is called as the Direct Cash Assistance of Village Fund which is expected to ease the economic burden of rural communities during the COVID-19 pandemic. The research was conducted using a qualitative method with a descriptive analytical approach. Data obtained through the literature studies. The results of this study found that there were complexities and several problems encountered in the implementation of the Village Fund Direct Cash Assistance distribution that tackled by the village.